Self-healing amyopathic dermatomyositis. - Garofalo, L.; Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A 3-year-old boy was first observed due to an acrolocated eruption, prevailing on the lower limbs and hands, asymptomatic, started 2-3 weeks after a virus infection of the upper respiratory tract. The personal history for atopy was negative, whereas there was a paternal grandmother with hand eczema and a maternal aunt with seasonal rhinitis. On physical examination, there was a lichenoid eruption mainly affecting the lower limbs (Fig. 1, 2), with an asymmetrical distribution sparing the typical sites of atopic dermatitis. The hematological and chemical examinations were within normal limits except for IgE 750 KU/L (n.v. for age up to 50) and AST 60 UI/L (n.v. up to 50). We hypotesized a lichenoid dermatitis and decided to monitor it without any treatment. We saw again the boy after 3 months in summer. The lichenoid dermatitis regressed almost completely. However, a heliotropic erythema appeared on his cheeks and nose (Fig. 3, box) and lichenoid papules on the dorsal aspect of his hands (Fig. 3) level with the articular surface of the metacarpophalangeal and interphalangeal joints, that were reminiscent of dermatomyositis.